Cognitive level of test Items and students’ achievement in mathematics among selected senior secondary school students in Ibadan (2016)
The study examined the effects of cognitive level of test items on academic performance of participants in multiple-choice questions in mathematics subject prepared by WAEC on senior secondary school students in Ibadan, Oyo State, Nigeria. Five hundred and twenty five students in SSS 3 were tested on a 50-item Mathematics Achievement Test. Their performances on cognitive level of test items were analyzed for,the purpose of this study. Results indicated that cognitive level of test items were significantly correlated with performance of participants in-mathematics multiple-choice question achievement test, and that participant performed well in lower level of cognitive domain than higher level of cognitive domain. Cognitive levels of test items arepredictive of students' achievement in mathematics, among the selected senior secondary school students, in Ibadan. Hence it is recommended that the teachers shouldexpose their learners tohigher levels of cognitive domain ofitems during teaching-learning process so as to enhance the students' achievement in mathematics.